Предмет: Алгебра, автор: pasunkodmitrij


lg(2x - 3) + lg(x - 1) = lg7 + lg3

Помогите, срочно нужно ​

Ответы

Автор ответа: Аноним
3

Ответ:

x=4.5

Объяснение:

\displaystyle\\lg(2x - 3) + lg(x - 1) = lg7 + lg3\\\\ODZ:\\\\\left \{ {{2x-3>0} \atop {x-1>0}} =>\right. ;x>1.5\\\\\\lg((2x-3)(x-1))=lg(7*3)\\\\(2x-3)(x-1)=21\\\\2x^2-3x-2x+3=21\\\\2x^2-5x-18=0\\\\D=b^2-4ac\\\\D=25+4*2*18=169=13^2\\\\x_1=(5-13)/4=-2\ \ ne\ udowl.odz\\\\x_2=(5+13)/4=4.5\\\\Otvet: x=4.5

Похожие вопросы
Предмет: Химия, автор: bodsheva